COVID-19 and myocardial injury - Herrey, AS; Mohiddin, SA; Letuka, p; Ntusi, NAB (SA Heart Journal, 2020)
The 2019 coronavirus pandemic (COVID-19), caused by SARS-CoV-2, has affected millions globally and has accounted for a multitude of deaths. Cardiovascular involvement with myocardial injury is common and is associated with severe morbidity and mortality. The pathophysiology of acute myocardial injury is complex and may include type I and type II myocardial infarction, direct damage to the cardiomyocytes, systemic inflammation, myocardial interstitial fibrosis, interferon mediated immune response, exaggerated cytokine response by Type 1 and 2 helper T cells, in addition to hypoxia. Angiotensin converting enzyme-2 receptors (ACE2-R) play a pivotal role in mediating viral entry into cells. Disruption of receptor signalling may also be the principal mechanism facilitating viral pathogenicity and altered ACE2-R biology may be a reason why patients with cardiovascular disease are more likely to be infected with SARS-CoV-2 and more likely to develop severe symptoms. New-onset hypertension, arrhythmia, myocarditis, heart failure, cardiomyopathy and coronary heart disease are among major cardiovascular disease comorbidities and complications seen in severe cases of COVID-19. As a surrogate for myocardial injury, multiple studies have shown increased cardiac biomarkers, mainly cardiac troponins I and T, in the infected patients – especially those with severe disease. Myocarditis is another cause of morbidity among COVID-19 patients.